BASED ON HEAT-TECHNICAL PARAMETERS OF THE AUTONOMOUS HYBRID HEAT SUPPLY SYSTEM OF MODEL VILLAGE HOUSES - Kamolov, Bekhzod; Davlonov, Khairulla; Tashmamatov, Bobir (Innovatsion texnologiyalar, 2023)
The article proposes a thermal scheme of a hybrid heat and hot water supply system based on vacuum solar collectors and heat pump devices for country houses and model houses. The heat-technical calculation of the hybrid heat and hot water supply system of the heat pump device connected to the vacuum solar collector and the underground heat source (sewage well) through the recuperator device is presented. The energy consumption of the heat pump device used in the hybrid heat supply system is based on having 2.5 kW, and as a result of the production of 12,5÷17,5 kW of heat energy for the heat and supply system, it is 5÷7 times more energy efficient than boiler devices and electric heating devices in traditional heat and hot water supply systems. Taking into account the meteorological climate parameters of the Kashkadarya region, the heating season is 132 days, in the hybrid autonomous heat supply system of the proposed rural houses and model houses, it is possible to save 39 600 kW·hours of electricity or 12÷14 tons of conventional fuel due to the use of only a 2.5 kW heat pump device. It is scientifically proven that savings can be made.